PENINGKATAN MUTU PENDIDIKAN ANAK-ANAK DI KAMPUNG JAWA - KOTA BATAM - Wisnu Yuwono; Johny Budiman; Ria Bintan; Andrea Putri; Anna Isabella Lau; Jennifer Jennifer; Kendy Setiawan Hartono; Lily Indrawati; Meilita Meilita; Tiara Shinta; Theresia Desilva (National Conference for Community Service Project (NaCosPro), 2020)
This community service program aims to improve children's education programs in Kampung Jawa - Batam City, considering that school-age children are still not proficient in numeracy, which is caused by limited infrastructure and experts. The method used here is the method of teaching while playing, using a game that we have designed with the method of "Advanced Counting After Playing 10 Times". Besides that, he also created an open donation movement on social media, to get proper textbooks. The result of the implementation that has been carried out is that there has been progressed in the education of school-age children where some children have started to recognize numbers and are starting to be able to add small numbers, and also thanks to the open donations we have made, children in Kampung Jawa-Batam now have lots of books to study.